PERANAN ORANG TUA MENDAMPINGI BELAJAR ANAK DIRUMAH ERA PANDEMIC COVID 19 KELAS VII SMP NEGERI 19 PONTIANAK - Hasanah, Nur; Asrori, Muhammad; Yuline, Yuline (Universitas Tanjungpura, 2023)
During the Covid-19 pandemic in Class VII SMP Negeri 19 Pontianak, the purpose of this study is to describe the role parents played in allowing their children to study at home. This study employs a quantitative descriptive approach. Data was gathered using methods other than tests, like questionnaires. There were 210 people in the study's population, and up to 63 people were sampled. The showed that during the COVID-19 pandemic Class VII SMP Negeri 19 Pontianak, parents played a